Impact response of laminated cylindrical shells - Carlos Alexandre Campos Pais Coelho; Fábio V.P. Navalho; P.N.B. Reis (Fracture and Structural Integrity)
Composite laminates subjected to low-velocity impact events on the through-thickness direction are conveniently studied and disseminated in the open literature. However, in terms of laminated cylindrical shells this subject is less common. Therefore, the main goal of the present work is to study the impact response of laminated composite cylindrical shells composed by different type of fibres. For this purpose, laminates with different configurations (6C, 2C+2K+2C and 2C+2G+2C), where the “number” represents the number of layers used and C=Carbon, K=Kevlar and G=Glass fibre layers, were analysed in terms of static and impact strength. It is possible to conclude that both static and impact performance are strongly influenced by the shells’ configuration. In terms of compressive static strength, the Kevlar hybrid shells present values 53.2% higher than the 6C shells, while the glass hybrid shells present values 17.3% lower. The impact analyses shows, regardless the similarity of the maximum loads for all configurations, that Kevlar hybrid shells achieved the highest elastic recuperation and the glass hybrid shells the maximum displacement.